1982
DOI: 10.1088/0029-5515/22/6/007
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and axisymmetric stability of dee-shaped plasmas in Doublet III

Abstract: Stable plasmas with surface elongations of up to 1.8 (aspect ratio = 3.4) have been produced in the upper lobe of Doublet III with the use of both passive and active controls. The growth rate of the vertical instability has been measured at various values of elongation by disabling the feedback circuit of the vertical position control power supply. A rigid-shift analysis of growth rates indicates that the passive stabilization effect of the field-shaping coils plays a key role in achieving a high elongation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…If there is no conductive material around the plasma, the growth rate of this instability is larger than 10 s s" 1 , which is too large for the feedback control to suppress the instability by practically feasible power supply. Growth rate reduction by the passive feedback effect of the conductive material has been confirmed experimentally in some tokamak devices [1][2][3]. This effect is necessary for vertical instability stabilization by practical power supply.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…If there is no conductive material around the plasma, the growth rate of this instability is larger than 10 s s" 1 , which is too large for the feedback control to suppress the instability by practically feasible power supply. Growth rate reduction by the passive feedback effect of the conductive material has been confirmed experimentally in some tokamak devices [1][2][3]. This effect is necessary for vertical instability stabilization by practical power supply.…”
Section: Introductionmentioning
confidence: 91%
“…The maximum growth rate in Doublet-Ill reported in Ref. [2] is also about 500 s" 1 , with the same type In Fig. 11, the decay rates of the exponentially changing response are adopted as data because JD for the oscillating response is not a good representation of the response characteristics.…”
Section: Time Response Of Feedback Controlmentioning
confidence: 99%
“…If the plasma duration time is shorter than the skin time of the shell, the positional instability is stabilized by the shell or the passive conductors [7][8][9][10][11][12][13][14][15][16]. For long-pulse operation, however, active feedback control is necessary to maintain the noncircular tokamak plasma in the centre [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Prime considerations were theoretical work [43] and reactor studies indicating that reactor-relevant values of (3 could be attained in dees. At the same time, the JAERI team [44] demonstrated that comparable performance could be obtained in such plasmas with fewer control problems than experienced with doublets. A powerful incentive was the ability to use the auxiliary heating power coming on line in a configuration of higher power density, by depositing heat in a single lobe rather than spreading it in the heating of doublets.…”
Section: Doublet III Plasmas With Auxiliary Heatingmentioning
confidence: 96%